Evaluation of the effect of P‐glycoprotein inhibition and induction on talazoparib disposition in patients with advanced solid tumours. Issue 4 (7th January 2020) - Elmeliegy, Mohamed; Láng, István; Smolyarchuk, Elena A.; Chung, Chin‐Hee; Plotka, Anna; Shi, Haihong; Wang, Diane
Abstract : Aims: In vitro data show that talazoparib is a substrate for P‐glycoprotein (P‐gp) and breast cancer resistance protein transporters. This open‐label, 2‐arm, drug–drug interaction Phase 1 study in patients with advanced solid tumours assessed the effect of a P‐gp inhibitor (itraconazole) and a P‐gp inducer (rifampicin) on the pharmacokinetics of a single dose of talazoparib. The safety and tolerability of a single dose of talazoparib with and without itraconazole or rifampicin were also assessed. Methods: Thirty‐six patients were enrolled (Arm A [itraconazole], n = 19; Arm B [rifampicin], n = 17). Patients in both arms received 2 single oral doses of talazoparib (0.5 mg, Arm A; 1 mg, Arm B) alone and with multiple daily oral doses of itraconazole (Arm A) or rifampicin (Arm B). Results: Coadministration of itraconazole and talazoparib increased talazoparib area under the plasma concentration–time profile from time 0 extrapolated to infinity by ~56% and maximum observed plasma concentration by ~40% relative to talazoparib alone. Coadministration of rifampicin and talazoparib increased talazoparib maximum observed plasma concentration by approximately 37% (geometric mean ratio 136.6% [90% confidence interval 103.2–180.9]); area under the curve was not affected relative to talazoparib alone (geometric mean ratio 102.0% [90% confidence interval 94.0–110.7]). Talazoparib had an overall safety profile consistent with that observed in prior studies in which talazoparib was administered as a single dose. Conclusion: Coadministration of itraconazole increased talazoparib plasma exposure compared to talazoparib alone. A reduced talazoparib dose is recommended if coadministration of potent P‐gp inhibitors cannot be avoided. Similar exposure was observed when talazoparib was administered alone and with rifampicin suggesting that the effect of rifampicin on talazoparib exposure is limited.